Screen‐printed electrode‐based homogeneous electrochemical aptasensor for mercury (II) based on reduced graphene oxide and exonuclease III‐driven cyclic reaction. Issue 9 (8th August 2022) - Lv, Zeping; Zhang, Mingli; Jin, Huali; Huang, Yawei; Wei, Min
Abstract: A novel disposable and portable electrochemical aptasensor based on reduced graphene oxide (RGO) was constructed for the detection of mercury (II) (Hg 2+ ) using methylene blue (MB) as the signal tag and exonuclease III‐induced cyclic reaction as signal amplification strategy. RGO was utilized as a carrier to immobilize MB‐DNA, and screen‐printed electrode (SPE) was used as the substrate electrode. The whole reaction was carried out in a homogeneous system, and finally, the target was detected directly in the solution using SPE, which did not require multiple fixation steps and simplified the experimental process. Under the optimized conditions, the developed electrochemical aptasensor had a wide linear range of 0.01–300 nmol L −1 with a low detection limit of 0.009 nmol L −1 and was successfully used for the determination of Hg 2+ in tap water samples. Furthermore, the aptasensor exhibited good stability and high selectivity. It had good application prospects in the detection of harmful substances in food. Abstract : A novel disposable and portable electrochemical aptasensor based on reduced graphene oxide was constructed for the detection of mercury (II) using exonuclease III‐induced cyclic reaction as a signal amplification strategy. The use of the designed DNA strand can greatly improve detection selectivity, and the employment of a homogeneous system can effectively save cost and simplify operation steps.